Treatment of Diabetic Ketoacidosis (DKA) with 2 Different Regimens Regarding Fluid Substitution and Insulin Dosage (0.025 vs. 0.1 units/kg/h) - Kapellen, T.; Vogel, C.; Telleis, D.; Siekmeyer, M.; Kiess, W. (Experimental and Clinical Endocrinology & Diabetes, 2012)
Diabetic ketoacidosis (DKA) is still the most dangerous acute complication in type 1 diabetes. The aim of this study was to compare treatment of DKA with a regimen of a low insulin dose (0.025 units/kg/h) vs. a standard insulin dose (0.1 units/kg/h).We retrospectively analysed all cases of children and adolescents (age 0–18 years) with type 1 diabetes and DKA who needed treatment in the ICU in the time period of 1998–2005 in 2 pediatric diabetes centers. In a chart review of the first 48 h after onset of DKA the following parameters where evaluated: pH, blood glucose, sodium, potassium, and ketones in urine. Consciousness, neurological status and complications such as cerebral edema, hypoglycaemia or hypokalemia were also recorded.23 children were treated in center A (low insulin dose) whereas 41 where treated in center B (standard insulin dose). Mean age of the patients was 8.9 (range 1.58–17.7) and 13.5 years (1.25–17.7) respectively (p=0.134). Mean pH was 7.1 and HCO3 was 9.05 and 7.79 respectively (p=0.122). Initial blood glucose was 26 mmol/l (no difference between the 2 centres). Treatment with the standard insulin dose resulted in a slightly shorter duration of acidosis (8 h in center A, 6.5 h in center B) and a significantly faster normalization of blood glucose (18 h in A, vs. 10.5 h in B) (p<0.005). During the first day we found similar and very low rates of hypoglycaemia. In center B one case of suspected cerebral edema and cerebral infarction occurred.Low dose insulin substitution is as safe as the recommended standard dose in respect to the occurrence of acute complications. Acidosis is broken slightly earlier with the standard dose. Implications of this earlier normalisation of pH remain unclear.
Keywords: type 1 diabetes mellitus; diabetic ketoacidosis; children; adolescents; treatment; insulin